Características da condição humana na contemporaneidade - Sell, Wilhelm (2009)
This work is an anthropological survey that exposes some features of human condition in postmodernity. The first part begins with two approaches: it starts by analyzing the anthropological lurch after the inception of left Hegelianism (FEURBACH and MARX) and thought of the aristocratic philosopher NIETZSCHE, highlighting the rupture with God and the increase in man s confidence in his potential, even regarding his redemption. Special attention is paid to some of this lurch s later developments, such as the weakening of being , which ensues after the rupture with the buoys that previously ensured its dignity. It concludes by examining the development of modern thought and its promising project for the progress of science and economy and for the strengthening of the state. The first part ends by contemplating some issues regarding the relationship between modernity and postmodernity, the mishaps, reform, and (dis)continuity, briefly touching upon some features of the human condition in the so-called postmodernity. In the second part, four eminent contemporary thinkers are considered: KONRAD LORENZ, PETER SINGER, RICHARD RORTY, and CHARLES MELMAN. Contributions for this survey are sought in their works, tracing different reflections that spring from man s inquiry into his existential condition. The works by the first three are inspected for new understandings that arise about the human being, which have replaced old concepts (sin, dignity and worth of life, truth, and solidarity), as well as foundations and justifications, giving them new meanings. Finally, MELMAN s critical analysis on the postmodern man is contemplated: the man without gravity. In the third and last chapter, the anthropological thoughts of two theologians, GOTTFRIED BRAKEMEIER and EULER WESTPHAL, are meditated upon, highlighting the issues on the human condition in postmodernity. The ambiguity of postmodern human existence is evidenced: neither is it possible to demonize this new stage of human history, nor should one be mislead by all the benefits stemming from the conveniences and discoveries with which one is bestowed. The work concludes by reflecting on some features of the human condition in postmodernity and by raising questions that were discussed earlier. In this context, theology is characterized as a critical science whose purpose is to fight for the reclaiming and the preserving of the sacredness of the human life and the cosmos. Furthermore, theology contributes for an anthropological analysis that contemplates the religious dimension as an essential component of man, expressed by promise, messianic expectation and eschatological hope; these expressions, both in modernity and postmodernity, are transferred from God to the human potential of creating/establishing, by means of institutions and the biotechnological science, the kingdom of heavens on earth.